2007
DOI: 10.1016/j.ibmb.2007.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the complete acetylcholinesterase gene (Ace1) from the mosquito Aedes aegypti with implications for comparative genome analysis

Abstract: Insensitive acetylcholinesterase (AChE) has been shown to be responsible for resistance to organophosphates and carbamates in a number of arthropod species. Some arthropod genomes contain a single Ace gene, while others including mosquitoes contain two genes, but only one confers insecticide resistance. Here we report the isolation of the full-length cDNA and characterization of the complete genomic DNA sequence for the Ace1 gene in the yellow fever mosquito, Aedes aegypti. The Ace1 homolog in other mosquito s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…As the target of organophosphorous (OP) and carbamate pesticides, it has received widely attentions. There are two ace genes in many insects such as Anopheles gambiae (Weill et al, ), Aphis gossypii (Li and Han, ), Schizaphis graminum (Gao et al, ), Culex pipiens (Huchard et al, ), Aedes aegypti (Mori et al, ), Culex tritaeniorhynchus (Nabeshima et al, ), Myzus persicae (Nabeshima et al, ), Rhopalosiphum padi , and Sitobion avenae (Chen and Han, ), Helicoverpa assulta (Lee et al, ), Plutella xylostella (Baek et al, ; Lee et al, ), and Bombyx mori (Chen et al, ). Two ace genes exist in most insects except Cyclorrapha suborder of Diptera (Huchard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As the target of organophosphorous (OP) and carbamate pesticides, it has received widely attentions. There are two ace genes in many insects such as Anopheles gambiae (Weill et al, ), Aphis gossypii (Li and Han, ), Schizaphis graminum (Gao et al, ), Culex pipiens (Huchard et al, ), Aedes aegypti (Mori et al, ), Culex tritaeniorhynchus (Nabeshima et al, ), Myzus persicae (Nabeshima et al, ), Rhopalosiphum padi , and Sitobion avenae (Chen and Han, ), Helicoverpa assulta (Lee et al, ), Plutella xylostella (Baek et al, ; Lee et al, ), and Bombyx mori (Chen et al, ). Two ace genes exist in most insects except Cyclorrapha suborder of Diptera (Huchard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, two ace genes were found in Aphis gossypii (Li & Han, 2002) and Anopheles gambiae (Weill et al ., 2002). Since then, two ace genes have been identified in many other insects, such as Culex pipiens (Huchard et al ., 2006), Aedes aegypti (Mori et al ., 2007), Culex tritaeniorhynchus (Nabeshima et al ., 2004), Myzus persicae (Nabeshima et al ., 2003), Rhopalosiphum padi and Sitobion avenae (Chen & Han, 2006) , Helicoverpa assulta (Lee et al ., 2006), Plutella xylostella (Baek et al ., 2005; Lee et al ., 2007) and Bombyx mori (Chen et al ., 2009). It has been suggested that the two ace s in insects originated from duplication before the diversification of arthropods (Labbe et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that both quantitative and qualitative changes in AChE conferred resistance to insecticides (Fournier et al, 1992(Fournier et al, , 1993. In insects, two different ace genes have been found in various species, such as Anopheles gambiae (Weill et al, 2002), Aphis gossypii (Li and Han, 2002), Culex pipiens (Huchard et al, 2006), Aedes aegypti (Mori et al, 2007), Myzus persicae (Nabeshima et al, 2003) and Bombyx mori (Seino et al, 2007). Some studies indicated that ace 1 gene transcripts are much more abundant than ace 2.…”
Section: Introductionmentioning
confidence: 99%